A holistic digital twin simulation framework for industrial facilities: BIM-based data acquisition for building energy modeling - Gourlis, Georgios; Kovacic, Iva (Frontiers in Built Environment, 2022)
Energy and resource efficiency as well as reduction of emissions are nowadays significant objectives for production companies. Industry 4.0, through extensive digitalization along the value chain, enables the achievement of these objectives not only in the construction of new facilities but in existing facilities as well. This requires an interdisciplinary approach, extending over production and logistic processes as well as the building, technical building services, and energy supply systems, consolidated through integrated modeling and simulation-based optimization. The research question this paper addresses is how to digitally couple these subsystems and optimize the overall system’s performance in terms of energy and resource efficiency, by distancing from silo-field thinking while employing an integrated analysis approach. The article briefly presents a holistic modeling and simulation framework, utilizing modular Digital Twins (DTs) of all elements that may constitute a given industrial unit. The integration of multiple DTs of these subsystems in a hybrid (continuous and discrete) simulation forms a holistic DT ecosystem of an existing facility. The particular focus of the study is the building representation in this DT ecosystem for energy-efficient production. Based on a methodology including hybrid simulation, Building Information Modeling (BIM), and visual programming, a semi-automated data acquisition workflow is proposed. The hybrid simulation is based on Discrete Event System Specification (DEVS) formalism, where the building is incorporated as a Building Energy Model (BEM). Within the abstracted representation of the overall system, the article explores the possibilities of parametrizing the DT of the building, interconnected with the rest of the factory elements, by acquiring information directly from existing BIM models. Through a comparative case study, the proposed workflow is compared to a manual one in terms of integrity and benefits. The study’s contribution lies in: 1) the detection of the required building level of abstraction for a holistic DT ecosystem; 2) the definition of the interconnections between the building-related counterparts and the rest of the virtual environment as well as the data required for their parameterization; 3) proposing a semi-automated workflow via virtual programming, for BIM-based creation of the building model within a holistic DT ecosystem.